1990
DOI: 10.1042/bj2680765
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cytochrome P450III and P450IV family proteins in streptozotocin-induced diabetes

Abstract: The effect of insulin-dependent diabetes on the hepatic microsomal activity of cytochrome P450III and P450IV family proteins was investigated in rats pretreated with streptozotocin. In order to discern between the effects of the diabetogen per se and those of the ensuing diabetes, streptozotocin-treated rats received in addition either nicotinamide to prevent the onset of diabetes or daily treatment with insulin to antagonize the effects of diabetes. Streptozotocin-treated rats displayed higher ethylmorphine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
38
1
2

Year Published

1993
1993
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(49 citation statements)
references
References 37 publications
8
38
1
2
Order By: Relevance
“…Moreover, CYP4A genes are coregulated with other genes that encode proteins involved in fatty acid β-oxidation (e.g., acetyl CoA oxidase and ketothiolase) and transport (liver fatty acid-binding protein and acyl-CoA-binding protein). It is therefore clear that CYP4A proteins are key intermediaries in an adaptive response to perturbation of hepatic lipid metabolism (43)(44)(45)(46). Consequently, the upregulation of CYP4A we have observed in MCD diet-fed Cyp2e1 -/-mice could be a physiological response in the unusual context of aberrant lipid accumulation and absence of CYP2E1 activity.…”
Section: Tablementioning
confidence: 81%
“…Moreover, CYP4A genes are coregulated with other genes that encode proteins involved in fatty acid β-oxidation (e.g., acetyl CoA oxidase and ketothiolase) and transport (liver fatty acid-binding protein and acyl-CoA-binding protein). It is therefore clear that CYP4A proteins are key intermediaries in an adaptive response to perturbation of hepatic lipid metabolism (43)(44)(45)(46). Consequently, the upregulation of CYP4A we have observed in MCD diet-fed Cyp2e1 -/-mice could be a physiological response in the unusual context of aberrant lipid accumulation and absence of CYP2E1 activity.…”
Section: Tablementioning
confidence: 81%
“…This time is congruent with the time over which propionate supplementation resulted in increased insulin concentrations. A relationship between insulin and cytochrome P450 expression was proposed when Barnett et al (1990) and Shimojo et al (1993) observed enhanced expression of cytochrome P450 3A during insulin-dependent diabetes, which was reversed by insulin replacement. Saad et al (1994) found a dose-dependent decrease in testosterone hydroxylation at the 6b position when rat hepatocytes were cultured with increasing concentrations of insulin (1, 10 and 100 nM), a reaction that is catalyzed primarily by the cytochrome P450 3A sub-family with minimal contribution from cytochrome P450 2C13 (Ryan and Levin, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CYP4A and CYP4F genes are differentially regulated by conditions that increase the flux of free fatty acids, such as fasting (47), high-fat diet (48), or T2D (49). CYP4A expression is increased under these conditions, whereas CYP4F expression is decreased.…”
Section: The Downstream Metabolism Of 1-deoxyso Is Mediated By Cyp4f mentioning
confidence: 99%